Rat maternal insulin resistance is associated with abnormal neurobehavioral response in offspring - Cuervo Sánchez, Marié Lucia (2019)
It is well established that maternal diet and metabolic state during pregnancy contributes to the risk of metabolic disease in offspring. Furthermore, recent epidemiological evidence suggests that gestational factors such as increased maternal obesity and impaired glucose metabolism can likewise affect offspring neurodevelopment, increasing the risk of neuropsychiatric disorders. We aimed to investigate the influence of long-term maternal fructose intake during preconception, gestation and lactation periods on neurobehavioral development of rat offspring. Wistar rats received either 10 % fructose enriched water or regular tap water for 20 weeks before and during gestation and through lactation. On P21, all littermates were separated and housed with ad libitum access to standard food and tap water. Control and fructose-fed mother’s blood samples were collected for biochemical analysis. Offspring behavior was evaluated using open field, social interaction, marble burying and T-Maze task performance tests. Data analyses were carried independently on male and female rats. Dams fed with a 10 % (w/v) beverage containing fructose showed a moderated body weight gain and significant increments in fasting glucose level, oral glucose tolerance test (OGTT) and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) index. Behavioral evaluation of the offspring revealed that females exposed to maternal fructose intake were prone to have increased number of marble buried and reduced learning performance in a T-maze compared to control-diet offspring. Our findings indicate that chronic maternal metabolic stress induced by a fructose-rich diet during pre- gestational, gestational and lactational periods showed a gender- specific increase in stereotyped repetitive behavior and working memory tasks in the offspring.